Population‐based study of the sensitivity of axillary ultrasound imaging in the preoperative staging of node‐positive invasive lobular carcinoma of the breast. Issue 8 (5th April 2018) - Morrow, E.; Lannigan, A.; Doughty, J.; Litherland, J.; Mansell, J.; Stallard, S.; Mallon, E.; Romics, L.
Abstract : Background: Preoperative staging of the axilla is important to allow decisions regarding neoadjuvant treatment and the management of the axilla. Invasive lobular carcinoma metastases are difficult to detect because of the infiltrative pattern of the nodal spread. In this study the sensitivity of preoperative axillary staging between invasive lobular (ILC) and ductal (IDC) carcinoma was compared. Methods: All women diagnosed with pure ILC or IDC in the West of Scotland in 2012–2014 were identified from a database maintained prospectively within the Managed Clinical Network. Pretreatment axillary ultrasound imaging (AUS), core biopsy and fine‐needle aspiration cytology (FNAC) results were compared between ILC and IDC. Results: Some 602 women with ILC and 4199 with IDC had undergone axillary surgery, of whom 209 and 1402 respectively had nodal metastases. Pretreatment AUS sensitivity was significantly lower in ILC than in IDC (32·1 versus 50·1 per cent respectively, P < 0·001; OR 0·47, 95 per cent c.i. 0·34 to 0·64). Core biopsy had equally high sensitivity of 86 per cent in both subtypes; however, FNAC was significantly less sensitive in both ILC (55 per cent; P = 0·003) and IDC (75·6 per cent; P = 0·006). Multivariable analysis revealed that cT3–4 status and symptomatic presentation were both significant in predicting nodal metastasis in patients with ILC and false‐negative AUS findings (OR 3·77, 95 per cent c.i. 1·69 to 8·42, P = 0·001; and OR 1·92, 1·24 to 2·98, P = 0·003, respectively). Conclusion: AUS is inferior in detecting axillary node metastasis in ILC compared with IDC. Women with cT3–4 lobular carcinoma may benefit from ultrasound‐guided axillary biopsy regardless of the ultrasonographic appearance of the nodes. Abstract : Less sensitive in lobular carcinoma